Pengaruh Model Pembelajaran Talking Stick Dipadu dengan Metode Pembelajaran Snowball Drilling terhadap Keterampilan Sosial dan Hasil Belajar Kognitif Siswa - Kusumayadi, Kusumayadi; Kalsum, Kalsum (Biocaster : Jurnal Kajian Biologi, 2022)
Differences in the characteristics of students cause teachers to find it difficult to choose learning methods so that teachers often use conventional learning methods. This results in a lack of interaction between students, and has an impact on the low social skills and cognitive learning outcomes of students. The purpose of this study was to describe the effect of the talking stick learning model combined with the snowball drilling learning method on the social skills of class X SMA Negeri 1 Kerambitan students and to determine the effect of the talking stick learning model combined with the snowball drilling learning method on the cognitive learning outcomes of class X SMA Negeri 1 students. kinship. This type of research is a quasi-experimental research, the design in this study using a pretest-posttest control group design, with a sampling technique using purposive sampling. The sample of this research is class X A as the experimental class and class X B as the control class. The instruments used in this study were the RPP implementation observation sheet, social skills observation sheet, and cognitive learning outcomes test. The data analysis technique used is descriptive quantitative and t-test. After analyzing the students' social skills data, the average percentage was 16.97 with a good category, while the post-test scores for the control class were 57.1 and the experimental class was 67.4. After testing the hypothesis, the price is obtained (tcount > ttable) or (3.102 > 1.671), so that the hypothesis is accepted, so it can be concluded that there is an effect of the talking stick learning model combined with the snowball drilling learning method on the cognitive learning outcomes of grade X students of SMA Negeri 1 Kerambitan in the academic year 2017/2018, and students' social skills are classified as good.